Estradiol Binds to Insulin and Insulin Receptor Decreasing Insulin Binding in vitro - Root-Bernstein, Robert; Podufaly, Abigail; Dillon, Patrick F. (Frontiers in Endocrinology, 2014)
Rationale: Insulin (INS) resistance associated with hyperestrogenemias occurs in gestational diabetes mellitus, polycystic ovary syndrome, ovarian hyperstimulation syndrome, estrogen therapies, metabolic syndrome, and obesity. The mechanism by which INS and estrogen interact is unknown. We hypothesize that estrogen binds directly to INS and the insulin receptor (IR) producing INS resistance. Objectives: To determine the binding constants of steroid hormones to INS, the IR, and INS-like peptides derived from the IR; and to investigate the effect of estrogens on the binding of INS to its receptor. Methods: Ultraviolet spectroscopy, capillary electrophoresis, and NMR demonstrated estrogen binding to INS and its receptor. Horse-radish peroxidase-linked INS was used in an ELISA-like procedure to measure the effect of estradiol on binding of INS to its receptor. Measurements: Binding constants for estrogens to INS and the IR were determined by concentration-dependent spectral shifts. The effect of estradiol on INS binding to its receptor was determined by shifts in the INS binding curve. Main Results: Estradiol bound to INS with a Kd of 12 × 10−9 M and to the IR with a Kd of 24 × 10−9 M, while other hormones had significantly less affinity. Twenty-two nanomolars of estradiol shifted the binding curve of INS to its receptor 0.8 log units to the right. Conclusion: Estradiol concentrations in hyperestrogenemic syndromes may interfere with INS binding to its receptor producing significant INS resistance.